Constructing Religio-Ritual Heritage: The New Shrine of Shekhsê Batê in Khetar, Northern Iraq - Spät, Eszter (Genius Loci Laszlovszky 60, 2018)

Falling into Book.’ Yezidi Seers in Modern Iraq - Spät, Eszter ((Hung.) In Spiritual Mediators (Hung.: Spirituális Közvetítők), 2014)

From sacred earth to magic squares: emerging literacy and creating Yezidi amulets in Iraq - Spät, Eszter (British Journal of Middle Eastern Studies, 2024)
Amulets have long been an integral part of the religious landscape of the Middle East. They attest not only to the antiquity and endurance of the belief in objects possessing the supernatural ability to protect (or harm) but also to the contacts between different religious groups and their complex impact on each other. One arresting example of how different religious traditions may influence one another and create new, hybrid forms is the recent appearance of amulets with inscriptions among the Yezidis of Northern Iraq. Based on extensive field research in Northern Iraq, the author argues that the emergence of written Yezidi amulets, the methods of their creations and the market for them bear witness to the phenomenon of religious crossover between the different religious communities, especially between Yezidis and Muslims, despite the often tense social relations between the two groups. Written charms also provide an insight into how the emergence of school-based literacy and the transformation from oral to bookish are reflected in the changing religio-magical customs of Yezidis.
Created from Fastlane, Scopus look-up

Gifts from the Sky: Yezidi Sacred Objects and Symbols of Power, Tools of Healing and Seals of Divine Favour - Spät, Eszter (Charms and Charming: Studies on Magic in Everyday Life, 2019)

On Soil and Jinn: Ritual Practices and Syncretism among the Yezidis of Iraq - Spät, Eszter (In Rituale als Ausdruck von Kulturkontakt: „Synkretismus” zwischen Negation und Neudefinition, 2013)

Religious Crossover in Northern Iraq: Interfaith Practices of Beseeching the Supernatural - Spät, Eszter (Faith and Doubt, 2020)

Shared Sacra in Northern Iraq: The Religious Other as the Source of Divine Mercy - Spät, Eszter ((Hung.) In Áldozat, istenítélet, divináció (Sacrifice, Ordeal, Divination), 2018)

The Book Revealing the Future in a Religion without Books: the Apocalyptic Visions of Yezidi Seers - Spät, Eszter (International Journal of Divination and Prognostication, 2021)
This article studies the “book,” or defter, of Yezidi seers in Northern Iraq. Following an oral religion in an Islamic environment where only “people of the Book” enjoyed legitimate status and social acceptance, Yezidis have developed various strategies to compensate for the absence of a written sacred book. The most unique among these is the phenomenon of “falling into book,” which refers to the altered state of consciousness experienced by some Yezidi seers. “Falling into book” provides the seer with a glimpse into both the past and the future, thus serving as a source of divination and prognostication, which ranges from addressing personal problems to foretelling the (usually apocalyptic) fate of the Yezidi community and the world. Thus the “book” of the seers is perceived to be a kind of “heavenly knowledge,” equal or even superior to the revealed texts of bookish religion